Pancytopenia associated megaloblastic anemia: a clinico-hematological study in a tertiary care hospital - Dr. Nitin Rohira; Dr. G. K. Sawke; Dr. Nilima Sawke (Tropical Journal of Pathology and Microbiology, 2019)
Background: Pancytopenia is a common and important clinical and haematological problem. It is a striking feature of many serious and life-threatening illnesses, ranging from simple drug-induced bone marrow hypoplasia, megaloblastic anemia to fatal bone marrow aplasias and leukemias. Thus, identification of the correct cause will help in implementing appropriate therapy and determine the better management and prognosis. Objectives: To study the clinical presentations and evaluate the hematological parameters including bone marrow aspiration in pancytopenia associated megaloblastic anemia cases. Materials and Methods: It was a prospective study, in which 75 cases of megaloblastic anemia associated with pancytopenia were evaluated clinically, along with hematological parameters and bone marrow aspiration in Department of Pathology, CMCH, Bhopal, over a period of one and half year. Results: Among 150 cases of pancytopenia studied, the commonest cause for pancytopenia was megaloblastic anemia (50%), followed by hperslenism (18%), and aplastic anemia (11%). Most of the patients presented with generalized weakness and fever. The commonest physical finding was pallor, followed by splenomegaly. Macrocytic normochromic red cells morphology was observed in 44(59%) patients of megaloblastic anaemia, followed by dimorphic blood picture in 20(27%) cases. The commonest marrow finding was hypercellularity with megaloblastic erythropoiesis. Conclusion: The present study concludes that in pancytopenia cases megaloblastic anaemia is a common and important clinical and haematological problem. Detailed primary hematological investigations along with bone marrow aspiration in pancytopenic patients are helpful for understanding of disease process and to diagnose or to rule out other causes of pancytopenia. These are also helpful in planning further investigations and management because many of them are completely curable while others are manageable.